Patient-reported outcomes in patients with resected, high-risk melanoma with BRAFV600E or BRAFV600K mutations treated with adjuvant dabrafenib plus trametinib (COMBI-AD): a randomised, placebo-controlled, phase 3 trial. Issue 5 (May 2019) - Schadendorf, Dirk; Hauschild, Axel; Santinami, Mario; Atkinson, Victoria; Mandalà, Mario; Chiarion-Sileni, Vanna; Larkin, James; Nyakas, Marta; Dutriaux, Caroline; Haydon, Andrew; Robert, Caroline; Mortier, Laurent; et al.
Summary: Background: In the phase 3 COMBI-AD study, patients with resected, stage III melanoma with BRAF V600E or BRAF V600K mutations received adjuvant dabrafenib plus trametinib or placebo. The primary analysis showed that dabrafenib plus trametinib significantly improved relapse-free survival at 3 years. These results led to US Food and Drug Administration approval of dabrafenib plus trametinib as adjuvant treatment for patients with resected stage III melanoma with BRAF V600E or BRAF V600K mutations. Here, we report the patient-reported outcomes from COMBI-AD. Methods: COMBI-AD was a randomised, double-blind, placebo-controlled, phase 3 study done at 169 sites in 25 countries. Study participants were aged 18 years or older and had complete resection of stage IIIA (lymph node metastases >1 mm), IIIB, or IIIC cutaneous melanoma as per American Joint Committee on Cancer 7th edition criteria, with BRAF V600E or BRAF V600K mutations, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients were randomly assigned (1:1) via an interactive voice response system, stratified by mutation type and disease stage, to receive oral dabrafenib (150 mg twice daily) plus oral trametinib (2 mg once daily) or matching placebos for 12 months. Patients, physicians, and the investigators who analysed the data were masked to treatment allocation. The primary endpoint was relapse-free survival, reported elsewhere. Health-related quality of life, reported here, was a prespecified exploratory endpoint, and was assessed with the European Quality of Life 5-Dimensions 3-Levels (EQ-5D-3L) questionnaire in the intention-to-treat population. We used a mixed-model repeated-measures analysis to assess differences in health-related quality of life between groups. This study is registered withClinicalTrials.gov, numberNCT01682083 . The trial is ongoing, but is no longer recruiting participants. Findings: Between Jan 31, 2013, and Dec 11, 2014, 870 patients were enrolled and randomly assigned to receive dabrafenib plus trametinib (n=438) or matching placebos (n=432). Data were collected until the data cutoff for analyses of the primary endpoint (June 30, 2017). The median follow-up was 34 months (IQR 28–39) in the dabrafenib plus trametinib group and 33 months (20·5–39) in the placebo group. During the 12-month treatment phase, there were no significant or clinically meaningful changes from baseline between groups in EQ-5D-3L visual analogue scale (EQ-VAS) or utility scores. During treatment, there were no clinically meaningful differences in VAS scores or utility scores in the dabrafenib plus trametinib group between patients who did and did not experience the most common adverse events. During long-term follow-up (range 15–48 months), VAS and utility scores were similar between groups and did not differ from baseline scores. At recurrence, there were significant decreases in VAS scores in both the dabrafenib plus trametinib group (mean change −6·02, SD 20·57; p=0·0032) and the placebo group (−6·84, 20·86; p<0·0001); the mean change in utility score also differed significantly at recurrence for both groups (dabrafenib plus trametinib −0·0626, 0·1911, p<0·0001; placebo −0·0748, 0·2182, p<0·0001). Interpretation: These findings show that dabrafenib plus trametinib did not affect patient-reported outcome scores during or after adjuvant treatment, and suggest that preventing or delaying relapse with adjuvant therapy could be beneficial in this setting. Funding: Novartis.